The remainder when 2 0 1 4 2 0 2 9 1 0 5 is divided by ( 2 0 1 4 2 0 1 4 − 1 ) can be expressed as a b . If a , b are integers. Find a + b
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
2 0 1 4 2 0 2 9 1 0 5 = 2 0 1 4 1 0 0 7 × 2 0 1 4 + 1 0 0 7 = 2 0 1 4 1 0 0 7 2 0 1 4 1 0 0 7 × 2 0 1 4
= 2 0 1 4 1 0 0 7 [ ( 2 0 1 4 2 0 1 4 − 1 ) n = 0 ∑ 1 0 0 6 2 0 1 4 2 0 1 4 n − 1 ]
= 2 0 1 4 1 0 0 7 ( 2 0 1 4 2 0 1 4 − 1 ) n = 0 ∑ 1 0 0 6 2 0 1 4 2 0 1 4 n − 2 0 1 4 1 0 0 7
Therefore, 2 0 1 4 2 0 2 9 1 0 5 ≡ 2 0 1 4 1 0 0 7 ( m o d 2 0 1 4 2 0 1 4 )
⇒ a = 2 0 1 4 and b = 1 0 0 7 ⇒ a + b = 3 0 2 1
Just observe a series for small nos. first
⇒ ( 3 5 ) m o d ( 3 3 − 1 ) = ( 3 5 m o d 3 ) ⇒ ( 4 7 ) m o d ( 4 4 − 1 ) = ( 4 7 m o d 4 ) . . . . . . ⇒ a b m o d a a = a b m o d a ⇒ { 2 0 1 4 2 0 2 9 1 0 5 } m o d { ( 2 0 1 4 2 0 1 4 ) − 1 } = 2 0 1 4 2 0 2 9 1 0 5 m o d 2 0 1 4 ⇒ i . e 2 0 1 4 1 0 0 7 ⇒ a + b = 3 0 2 1
Problem Loading...
Note Loading...
Set Loading...
2 0 1 4 2 0 1 4 − 1 ≡ 0 mod ( 2 0 1 4 2 0 1 4 − 1 ) ⇒ 2 0 1 4 2 0 1 4 ≡ 1 mod ( 2 0 1 4 2 0 1 4 − 1 ) ⇒ ( 2 0 1 4 2 0 1 4 ) 1 0 0 7 ≡ 1 1 0 0 7 ≡ 1 mod ( 2 0 1 4 2 0 1 4 − 1 ) ⇒ 2 0 1 4 2 0 2 8 0 9 8 ≡ 1 mod ( 2 0 1 4 2 0 1 4 − 1 ) ⇒ 2 0 1 4 2 0 2 8 0 9 8 × 2 0 1 4 1 0 0 7 ≡ 1 × 2 0 1 4 1 0 0 7 mod ( 2 0 1 4 2 0 1 4 − 1 ) ⇒ 2 0 1 4 2 0 2 9 1 0 5 ≡ 2 0 1 4 1 0 0 7 mod ( 2 0 1 4 2 0 1 4 − 1 ) As, 2 0 1 4 1 0 0 7 < 2 0 1 4 2 0 1 4 − 1 , 2 0 1 4 1 0 0 7 is the desired reminder. Thus the answer is 2 0 1 4 + 1 0 0 7 = 3 0 2 1